(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
This study presents a comprehensive overview of contemporary developments in Gorenstein homological algebra (GH-algebra), with Special Consciousness in relative framework which overcame the classical constraint of isotropic dimensions in irregular rings. We suggest a methodological development of Gorenstein projective, injective, and flat modules (Gproj, inj and F-Mod), moving from their initial conceptualization in the mid-1990s to recent generalizations involving semidualizing modules(S-Mod) and Foxby classes(F-classes). This article highlights the important role of test modules(T-Mod) in detecting the finiteness of homological dimensions(H-dimensions), effectively generalizing the classical Auslander–Buchsbaum–Serre theorem (ABS theorem) for irregular environments. Furthermore, we examine the applications of relative Gorenstein homological algebra (GH-algebra) in reformulating foundational results, such as the relative Gorenstein counterpart of Hilbert’s Syzygy Theorem (GC-Hilbert’s Syzygy Theorem). The paper also covers the latest breakthroughs for 2024–2026 and 2026. which includes a classification of acyclic Auslander–Gorenstein algebras (AG-algebras) and results on the idea of τ-tilt(τ-t) over skewed group monomial algebras to rank them Broken trends, the article identifies crucial gaps in in current literature such as the projective flat (pro-flat) problem and analogs over group rings and an integrated theoretical roadmap. This study is an essential and useful resource for researchers. and graduate students trying to navigate an increasingly complex of ring theory, representation theory (R-theory) and relative homological algebra (RH-algebra).